Association between matrix metalloproteinases-2 and -9 gene polymorphism with basement membrane disruption in oral lichen planus: A case-control pilot study - Anubhuti Sood; Latha Mary Cherian; R. Heera; Sanish Sathyan; Moinak Banerjee (Journal of Oral Biology and Craniofacial Research)
Objectives: This study investigated genetic polymorphism of matrix metalloproteinases (MMP) −2 and −9 in oral lichen planus (OLP) and their association with the basement membrane status. Study design: This case-control study involved genotyping of peripheral blood sample of 32 OLP patients and 106 ethnically matched controls. Single nucleotide polymorphisms (SNP) that were assessed in the groups were- MMP9 rs3918242, MMP9 rs17576 and MMP2 rs865094. Basement membrane status of the OLP biopsy samples was microscopically assessed and recorded following Periodic acid Schiff staining. Results: MMP9 rs3918242 showed significant genotypic and allelic associations between OLP subjects and controls. It was also significantly associated with intact basement membranes in OLP cases with increased frequency of ‘TT’ genotype and ‘T’ allele. No association was found with regard to MMP9 rs17576 and MMP2 rs865094. Conclusion: Biallelic substitution at the promoter region of MMP9 (rs3918242) gene may be associated with increased risk of development of OLP. It may be involved in compromising the integrity of the basement membrane junction.